Kesaksian Perempuan Dalam Hadis Nabi - Marhumah, Ema (Sunan Kalijaga State Islamic University & The Asia Foundation, 2009)
The provision of women's rights to become witneses promoted by Islam during the life of the Prophet Muhammad was indeed a high achietlement considering the tradition of the era which did not recognize women's rights to become witnesses in legal affairs. The Prophet permitted women to act as witnesess not only on trade, but also in courts for public disputes. This is because the essential thing in the affair of giving witness does not lie in the type of the sex of the witness, but on the capacity, expertise of the witness in performing their task to attain justice. In short there is no preference in the sex of a witness; men and women have rights become witnesses as far as they have intellectual cabability to do so.